1998
DOI: 10.1063/1.368138
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure of carbon rich a-SiC:H films and the influence of gas and heat treatments

Abstract: Articles you may be interested inReduction of hydrogen-induced optical losses of plasma-enhanced chemical vapor deposition silicon oxynitride by phosphorus doping and heat treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…However, as T a further increases from 400 to 700 8C, the intensity of C-H bonds gradually decreases, caused by the disruption of C-H bonds at T a above 400 8C. This is in good agreement with what has been reported by Friessnegg et al [24] who find that C-H bonds in the a-SiC:H films start to dissociate at T a slightly above 400 8C. The absorption band at $780 cm À1 is attributed to the Ge-C stretching vibration [1,2,17], and no significant changes in the line shape and intensity for the Ge-C peak occur with increasing T a up to 400 8C.…”
Section: Bonding Structuresupporting
confidence: 93%
“…However, as T a further increases from 400 to 700 8C, the intensity of C-H bonds gradually decreases, caused by the disruption of C-H bonds at T a above 400 8C. This is in good agreement with what has been reported by Friessnegg et al [24] who find that C-H bonds in the a-SiC:H films start to dissociate at T a slightly above 400 8C. The absorption band at $780 cm À1 is attributed to the Ge-C stretching vibration [1,2,17], and no significant changes in the line shape and intensity for the Ge-C peak occur with increasing T a up to 400 8C.…”
Section: Bonding Structuresupporting
confidence: 93%
“…In previous studies, authors have primarily utilized FTIR to determine either the hydrogen content or the concentration of some other single element in a dielectric material. In a few cases, other researchers have utilized previously published values for K SiC , K SiH , and K CH to calculate the total Si-C, Si-H, and C-H bond densities in a-SiC:H thin films [57,[60][61][62]. Unfortunately, in none of these reports were elemental or mass densities computed and/or cross calibrated to other techniques.…”
Section: Ftir Density and Elemental Composition Analysismentioning
confidence: 95%
“…Quantitative FTIR measurements of bond concentrations in a-SiC x and a-SiC x :H films have been reported by others [57][58][59][60][61][62]. These studies have typically relied on IR absorption cross sections reported for individual chemical bonds in non-SiC:H films.…”
Section: Introductionmentioning
confidence: 97%
“…The Ar + ion sputtering and annealing process does not produce a stoichiometric, single crystalline SiC surface. It leaves the surface with many defects and an excess of carbon because the Si preferentially evaporates during annealing [19][20][21][22]. The cleaning treatment does, however, remove the C, P, and Fe deposited during the course of experiments and does create a highly reproducible surface.…”
Section: Methodsmentioning
confidence: 96%